Covid-19 Pandemic And Sustainabilitystudy At Madrasah Ibtidaiyyahpsm Sulursewu, Teguhan, Ngawi, East Java - Moh. Toriqul Chaer; Muhammad Atabiqul As'ad; Qusnul Khorimah; Erik Sujarwanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Indragiri, 2020)
The continuity of learning programs during the COVID-19 pandemic found educational institutions, especially Madrasah Ibtidaiyyah Pesantren Sabilil Muttaqien (PSM) temporarily closed the learning process in schools. To prevent the spread of COVID-19 that is currently engulfing Indonesia. Lack of preparation, readiness and learning strategies have a psychological impact on teachers and students. Declining quality of skills, lack of supporting facilities and infrastructure. Learning from home (online) is an effort by the government program to ensure the continuity of learning in the pandemic period. The research method uses participatory action research (PAR), which focuses on understanding social phenomena that occur in the community and mentoring efforts on the problems faced. The assistance effort is to help the children of MI Sulursewu, Ngawi in participating in online learning related to; 1). Preparation of activities, 2). Counselling participants offline method, 3). Offline activities method. Results of the study show that the mentoring activities following the target of achievement; first, the activity can be carried out following the schedule that has been set. Second, students are always on time for the online learning hours that have been set. Offline methods show that efforts can help ease the burden on parents, but can also make it easier for students to receive subject matter.